Whistling in the dark a novel - Hughes, Shirley 1927-2022 (Walker Books, 2015)
Joan and her family live in Liverpool during the Blitz, doing their best for the war effort, and befriending a Polish refugee. One day they encounters a mysterious man and must decide whether to help him